PENGARUH KONSENTRASI KARAGENAN DARI Kappaphycus alvarezii TERHADAP KARAKTERISTIK FISIKOKIMIA DAN SENSORIS JENANG DODOL BERBASIS BUAH SALAK (Salacca zalacca) - Handini Handini; Hendrikus Nendra Prasetya; Baddi Saeppunuk (BUANA SAINS, 2026)
Snake fruit (Salacca zalacca) is a local commodity with high perishability, necessitating product diversification. This study aimed to evaluate the effect of carrageenan concentrations (0%, 3%, 5%, 7%, 9%) on the physicochemical (reducing sugar content, L*a*b* color, tensile strength) and organoleptic (taste, overall) properties of snake fruit jenang dodol. A completely randomized design (CRD) with 5 treatments and 3 replicates was applied. Physicochemical data were analyzed using ANOVA (?=0.05) followed by Duncan’s test, while organoleptic data were analyzed using the Friedman test. Results showed that the addition of carrageenan had no significant effect on any parameter (p0.05). The highest reducing sugar content (6.49%), lightness (49.90), tensile strength (0.2873 N), and the highest preference scores for taste (1.80) and overall (2.10) were all obtained in the control treatment (0% carrageenan). It is concluded that carrageenan up to 9% does not improve the physicochemical or sensory quality of snake fruit jenang dodol.